SEBARAN SPASIO-TEMPORAL IKAN YANG TERTANGKAP DENGAN JARING PANTAI DI PERAIRAN TELUK AMBON BAGIAN DALAM [Spatio-temporal distribution of fishes catched by beach seine in inner Ambon Bay] - O. T.S Ongkers; M. Boer; I. Muchsin; S. Sukimin; K. Praptokardiyo (Jurnal Iktiologi Indonesia, 2009)
Study on spatio-temporal distribution of fishes caught by beach seine was carried out in Inner Ambon Bay during a year. The aim of this study is to describe the distribution of fishes in three zones, which they are zone of Halong, Lateri, and Waiheru every month during a year. The result showed that Waiheru zone at the dark of moon has many species of fishes. Shorthead anchovy, gold spot herring, and Indian anchovy were always found every month although they were no plenty. Species similarity of Waiheru zone was closed to Lateri zone, and there were five clusters of month of species association during a year. It was concluded that existence of fishes was depended by zone (location) and month (period).